Synergy of Oxygen Plasma and Al2O3 Atomic Layer Deposition on Improved Electrochemical Stability of Activated Carbon-Based Supercapacitor - Zhang, Fuming; Song, Guanghui; Gandla, Dayakar; Ein-Eli, Yair; Tan, Daniel Q. (Frontiers in Energy Research, 2021)
As a conventional electrode material of electric double-layer capacitors (EDLC), activated carbon (AC) still faces challenges withholding it from exhibiting high capacitance and durability at a higher voltage. Here, we introduce a combined method of oxygen plasma and Al2O3 atomic layer deposition (ALD) on AC electrodes enabling the reduction of the impedance and improve the cycle stability of the EDLC. The defect structure can be precisely designed by merely tuning the oxygen-plasma treatment time, thereby affecting the microstructures of AC electrode. Such an approach permits the introduction of the first-operated AC electrode with more defects and ALD passivation of the AC resulting in an outstanding rate performance for the device (40.6 F g-1 at 5 mA cm-2, 20.1 Fg-1 at 100 mA cm-2) and cycling stability ( 90% retention after 5000 cycles). This synergistic effect of defects from doped oxygen and stable aluminum oxide layer on the electrode surface is pronounced. This work provides a feasible strategy to construct a durable AC material with a superior supercapacitor cycling performance.